THE DEVELOPMENT OF CLINICAL RISK MANAGEMENT IMPLEMENTATION MODEL IN IMPROVING QUALITY AND PATIENT SAFETY - Agnes Nathania Yostin; Nofierni Nofierni; Anastina Tahjoo (Jurnal Health Sains, 2023)
Clinical risk management plays an important role for hospitals in promoting patient safety and improving service quality in order to reduce or prevent risk related to patient care. The purpose of this study was to develop a model for implementing clinical risk management in improving quality and patient safety in class C private hospital in West Jakarta. This research using Participatory Action Research method. Participants in this study amounted to 20 people divide into 8 clinical units in the hospital. Data were collected using focus group discussions (FGD), using observation sheets, and quantitative assessment using questionnaires. Qualitative data analysis was performed by content analysis and quantitative data analysis using Wilcoxon test. The results of this study are clinical risk register model as a form of clinical risk management implementation, 8 clinical units in the hospital had clinical risk registers and the result of Wilcoxon test showed that there were significant differences in the level of participant knowledge about clinical risk management before and after the implementation (Asymp. Sig. value of 0.000 < α 0.05).